2014
DOI: 10.1093/database/bau058
|View full text |Cite
|
Sign up to set email alerts
|

Curation accuracy of model organism databases

Abstract: Manual extraction of information from the biomedical literature—or biocuration—is the central methodology used to construct many biological databases. For example, the UniProt protein database, the EcoCyc Escherichia coli database and the Candida Genome Database (CGD) are all based on biocuration. Biological databases are used extensively by life science researchers, as online encyclopedias, as aids in the interpretation of new experimental data and as golden standards for the development of new bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…This benefitted CTD in many ways. Instead of relying on co-mentioned terms from an abstract, CTD had Ph.D.-level scientists reading the primary literature and coding the authors’ detailed results in a computable format, increasing the accuracy and reliability of the information ( 10 , 11 ). In 2006, we produced MEDIC ( 12 ), a resource of merged OMIM ( 13 ) and MeSH ( 14 ) disease terms, allowing biocurators to additionally capture chemical–disease (C–D) and gene–disease (G–D) relationships using a robust and hierarchical controlled vocabulary.…”
Section: Ctd's 10th Year Anniversarymentioning
confidence: 99%
“…This benefitted CTD in many ways. Instead of relying on co-mentioned terms from an abstract, CTD had Ph.D.-level scientists reading the primary literature and coding the authors’ detailed results in a computable format, increasing the accuracy and reliability of the information ( 10 , 11 ). In 2006, we produced MEDIC ( 12 ), a resource of merged OMIM ( 13 ) and MeSH ( 14 ) disease terms, allowing biocurators to additionally capture chemical–disease (C–D) and gene–disease (G–D) relationships using a robust and hierarchical controlled vocabulary.…”
Section: Ctd's 10th Year Anniversarymentioning
confidence: 99%
“…In life sciences, manual expert curation plays a fundamental role in the creation of high quality knowledgebases. Manual curation is acknowledged to be highly accurate 1 , 2 , but criticism is often raised about the necessity for such a time- (and cost-) consuming activity as opposed to the use of programs for automated or semi-automated information extraction (Information-Extraction programs—IE programs). In reality, current IE programs are not able to extract the large amount of information or compare data with the same accuracy as professional curators do, but they can be extremely useful for identifying mentions of single entities in the scientific publications, using for instance name-entity recognition tools 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent study of ours has shown the accuracy of manual curation to be very high (1.4% error rate for EcoCyc, 1.8% error rate for Candida Genome Database) (6). Thus, the 33 IEPs for recognizing single relations surveyed by (4, 5) have error rates that are 14–42 times higher than the error rates of manual curation.…”
Section: Text Mining As An Alternative To Professional Curationmentioning
confidence: 67%